2015
DOI: 10.3126/banko.v25i1.13467
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and cytotoxic properties of selected medicinal plants from Kavrepalanchowk, Nepal

Abstract: Antibacterial properties of Nepalese plant species -Myrica esculenta, Mahonia nepaulensis, Madhuca longifolia and Schima wallichii were evaluated on human pathogenic microorganisms: Salmonella typhi, Staphylococcus aureus and Escherichia coli. The plants were found to possess phytochemicals-saponins, glacosides, flavonoids, tannins and alkaloids. Methanolic extract from these plants showed antimicrobial activity against tested organisms. Similarly, Brine shrimp lethality test of extracts showed the LC50 values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Used against different disease conditions such as; antidiabetic, antiallergic, antimicrobial, anti-ulcer, antihypertensive, antioxidant, and higher phenolic and flavonoid compounds including myricetin, myricanol, and myricanone have anti-inflammatory properties. [44].…”
Section: Myrica Esculenta Myricaceaementioning
confidence: 99%
“…Used against different disease conditions such as; antidiabetic, antiallergic, antimicrobial, anti-ulcer, antihypertensive, antioxidant, and higher phenolic and flavonoid compounds including myricetin, myricanol, and myricanone have anti-inflammatory properties. [44].…”
Section: Myrica Esculenta Myricaceaementioning
confidence: 99%
“…In the acute toxicity test, a previous study showed that the aqueous extracts of P. guajava and P. amarus leaves did not induce any mortality or any histological renal and fetal disorders of the treated rats [21]. Using the brine shrimp lethality test, Gyawali et al [41] showed that the crude methanolic extract of the S. wallichii bark was mildly toxic and it was suggested to use for human consumption for drug purposes. Together with our cytotoxicity test, the data confirm the safety of the selected aqueous plant extracts in the traditional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Nepal is being a habitat for more than ten thousand herbs in its alpine belt representing 6076, as flowering plants under 1534 genera and 216 families. About 5% of herbal plants are endemic to the country, while almost 30% of herbal plants are habituated in the Himalayan range (Gyawali et al 2020). The database listing for Nepal shows 1624 species of medicinal and aromatic species (Bhattarai & Karki 2004).…”
mentioning
confidence: 99%
“…It is traditionally used to treat dysentery, inflammation to the eyes, antibacterial, and antioxidant properties (Manandhar 1991; Jian-Ming & Qing 2015). The methanolic extract of M. napaulensis showed a broad spectrum of antimicrobial activity which might be due to the presence of alkaloids and flavonoid (Gyawali et al 2020). Ethanolic extract of Mahonia leaves and bark are good anti inflamatory properties and antioxidant candidates (Nguyen et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation